IN VITRO DIRECT ORGANOGENESIS OF LINDERNIA DUBIA (L.) PENNELL - G. Karuniya Raja Viella; Amzad Basha Kolar; G. Jahirhussain (The Bioscan, 2025)
Lindernia dubia (L.) Pennell a least concerned emergent plant belong to the family linderniaceae was subjected to micropropagation technique for the standardization of in vitro direct organogenesis protocol. The experiment was carried out to explore, conserve and increase the distribution of the plant via aseptic condition and this serves as the first report of this plant species. Nodal segment from the elite mother plant was excised, surface sterilized and inoculated in Plant Growth Regular (PGR) Free MS basal medium for organogenesis following the standard plant tissue culture procedure. The strength of the MS salt was altered for obtaining the best regeneration capacity in both the medium. The result showed that half strength - Plant Growth Regulator free medium regenerated more plantlets from the selected explant than the other medium. In Hormone free MS media, only MS salt, Carbon source and B5 Vitamins were added. After a month of inoculation, the developed shootlets were sub cultured and raw data's for shoot & root number, length were calculated at 25 th and 50th day from incubation. Statistical interpretations like ANOVA and Tukeys Multiple comparision Analysis were performed for significance. The regeneration percentage was 100 in all the sets. So, from the study it is concluded that the plant naturally possess essential growth regulators for its vegetative phase and under artificial conditions like in vitro conditions they doesn’t require specific growth regulators.